Relationship between stomatognathic alterations and idiopathic scoliosis: a systematic review with meta-analysis of observational studies - Francisca Gámiz-Bermúdez; Alfonso Javier Ibáñez-Vera; Esteban Obrero-Gaitán; Irene Cortés-Pérez; Noelia Zagalaz-Anula; Rafael Lomas-Vega (EFORT Open Reviews, 2023)
Purpose: The objective of this systematic review was to assess a possible relationship between stomatognathic alterations and idiopathic scoliosis (IS). Design: This study is a systematic review with meta-analysis of observational studies. Methods: The protocol of this systematic review with meta-analysis was registered in PROSPERO (CRD42022370593). A bibliographic search was carried out in the Pubmed (MEDLINE), Scopus, Web of Science and CINAHL databases using the MeSH terms ‘Scoliosis’ and ‘Stomatognathic Disease’. The odds ratio (OR) of prevalence and standardized mean difference (SMD) were used to synthesize the results. Results: Of 1592 studies located, 14 studies were selected with 3018 subjects (age: 13.9 years). IS was related to Angle’s class II (OR = 2.052, 95% CI = 1.236–3.406) and crossbite (OR = 2.234, 95% CI = 1.639–3.045). Patients with malocclusion showed a higher prevalence of IS than controls (OR = 4.633, 95% CI = 1.467–14.628), and subjects with IS showed high overjet (SMD = 0.405, 95% CI = 0.149–0.661) and greater dysfunction due to temporomandibular disorders (SMD = 1.153, 95% CI = 0.780–1.527). Conclusion: Compared with healthy controls, subjects with IS have twice the risk of suffering from occlusion disorders, present greater temporomandibular dysfunction and have a greater overjet in the incisors. Moreover, subjects with malocclusion have an IS prevalence up to four times higher. The systematic orofacial examination of patients with IS should be recommended.